Explaining the Informal Sector in Indonesia from the Transaction Costs Perspective - Gultom, Yohanna M. L. (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2014)
The informal sector in Indonesia is massive, and has become a challenge to the growth of the open market economy. Explanations of the cause of informality have shifted over time from structural dualism to excessive government regulation. This paper argues that merely focusing on the high cost regulation may not reveal the bottom line of informality. Assessment and elaboration of infomality need the help of the transaction cost approach that suggests that informality in the economy exists due to the high-transaction-cost institutional framework. To support the argument, this paper provides a preliminary study on the transaction costs borne by firms in the industrial manufacturing sector based on two industrial surveys conducted by BPS-Statistics Indonesia, which are the 2009 survey on medium and large-scale enterprises (MLEs) and the 2010 survey on micro and small-scale enterprises (MSEs). This paper shows that micro and small-scale enterprises with no legality bore the least transaction costs compared to those operating legally, both micro and small-scale, as well as medium and large-scale enterprises. Consequently, regulatory reforms aimed at reducing transaction costs, not merely aimed at reducing official costs and simplifying procedures, are the keys to achieving economic growth while ensuring full participation of the private sector.